Impact ofSystemic Insecticide Applicationon populationsElaeidobius kamerunicus Faust(Coleoptera: Curculionidae) on Oil Palm Plantation - yeni rawati harianja; Suzanna Fitriany Sitepu; Marheni sembiring (Universitas Sumatera Utara, 2018)
Oil palm is one of the commodity crop that has an important role in the economy in Indonesia. The main problems encountered are low productivity caused by the decline in population of oil palm pollinating insects Elaeidobius kamerunicusFaust.The purpose of this study was to examine the effect of systemic insecticides on E. kamerunicuspalm oil plantations in PTPN IV Marihat, Pematang Siantar. This research was conducted at Indonesian Oil Palm Research Institute (IOPRI), Pematang Siantar collaboration with PTPN IV. The methodwasfactorial randomized block designwith two factors and three replications. The first factor was type of active ingredient ( asefat dimehipo, klorantraniliprol), the second factor was dose insecticide (5 gr, 10 gr, 20 gr) and (7.5 ml, 5 ml, 10 ml). The parameters were observed consisting are total population of E.kamerunicusper hectare and sex ratio. The results showed thatthe total decrease in the population of E. kamerunicus 90 days after application was 18% of the inifialpopulation. Sex ratio of E. kamerunicus was1:1.5. Keywords :Acephate, Dimehypo, Elaeidobius kamerunicus, Klorantraniliprol, systemic insecticide